Rhetorical Move and Language Feature Analysis on Multilingual Research Article Abstracts Across English, Indonesian, and Arabic Languages in Islamic Studies - Yudhiantara, Rully Agung; Kurniawan, Eri; Al Farisi, Mohamad Zaka (UIN Sunan Gunung Djati Bandung, 2025)
Research article abstracts play a critical role in academic communication, particularly in Islamic education, as they serve as a gateway for readers to access and evaluate scholarly contributions. This study investigates the rhetorical moves and linguistic features of trilingual paired abstracts (English, Indonesian, and Arabic) in Islamic studies research articles. Using a corpus-based approach and contrastive linguistic analysis, the study examines how authors structure their abstracts and employ linguistic strategies across these three languages. The findings reveal that all three languages follow Hyland’s five-move framework, with Moves 2 (Purpose), 3 (Method), and 5 (Conclusion) being the most common. In contrast, Move 4 (Product) emerged as obligatory across the corpus. At the step level, Step 8 (context and procedures) dominated in the Method move, and Steps 6 and 7 were prevalent for Move 3, while Steps 11 and 12 were rarely used in Move 5. Linguistically, there is a consistent preference for the present tense and active voice, with English abstracts heavily favoring the present tense and Indonesian abstracts relying on non-conjugated verbs. These results have practical implications for language departments in Islamic higher education institutions, guiding the development of academic writing curricula. They also offer insights for researchers in Islamic studies to craft effective abstracts and manuscripts aligned with international academic conventions.